Encapsulation and melanization. The mealybug defends itself against a natural enemy-but loses - Sullivan, D.J. (1981)
The cassava mealybug has a defense mechanism against its natural enemy Epidinocarsis lopezi. When the female wasp lays its eggs inside the mealybug, the mealybug`s blood cells surround or encapsulate the parasitoid`s egg or larvae. This is followed by a hardening or blackening of the capsule, called melanization, resulting in suffocation and death. However, it seems that the mealybug`s blood cells are not capable of encapsulating several eggs or larvae so one survives to kill the mealybug. (CIAT)